2022
DOI: 10.1155/2022/6358188
|View full text |Cite
|
Sign up to set email alerts
|

Satellite In-Orbit Secondary Collision Risk Assessment

Abstract: The massive mega constellation of satellites will have a significant impact on global space safety. With Starlink as an example, this paper is aimed at assessing the risk of in-orbit collision, analyzing the probability of collision in orbit in its natural operating state, and forecasting the probability of secondary collision between the collision-generated short-term debris cloud and satellites in the same orbit. The mass, size, velocity, and direction of space debris in a particular orbit of Starlink satell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…This section delves into the prospective ramifications of Kessler's Syndrome, envisioning a scenario where satellite communication is entirely compromised over the span of two to three decades, and explores its profound implications on humans. The authors highlight the increasing risk of collisions between active space vehicles and space debris, an effect attributed to the increase in the affordability of satellite launches and the commercialization of the space industry Tao et al (2022). Understanding the gravity of such a prospect is vital for informed decision-making and robust contingency planning.…”
Section: Impact On Major Sectors Without Satellitesmentioning
confidence: 99%
“…This section delves into the prospective ramifications of Kessler's Syndrome, envisioning a scenario where satellite communication is entirely compromised over the span of two to three decades, and explores its profound implications on humans. The authors highlight the increasing risk of collisions between active space vehicles and space debris, an effect attributed to the increase in the affordability of satellite launches and the commercialization of the space industry Tao et al (2022). Understanding the gravity of such a prospect is vital for informed decision-making and robust contingency planning.…”
Section: Impact On Major Sectors Without Satellitesmentioning
confidence: 99%
“…With the rapidly acceleration of satellite deployments by nations and commercial companies, the number of debris has increased significantly in recently years [1] [2]. For the safety of in orbit spacecrafts and the development of future space activities, it is necessary to remove these debris and slow down its growth [3]- [7].…”
Section: Introductionmentioning
confidence: 99%
“…Luciano Anselmo et al introduced a specific critical index of collision rate percentage growth to assess the environmental impact of large satellite constellations in near-Earth orbit [15]. The results of this index, which was calculated for various constellations and applied at altitudes ranging from 800 km to 1400 km, show that in regions of space where the current catalogued debris density is already high, such as around 800 km, adding 100 more abandoned satellites would increase the current collision rate by about 10%; in less-crowded low-orbit regions, such as near 1110 km and 1325 km, adding 100 more abandoned satellites would increase the current collision rate by about 10%; and in less-crowded high-orbit regions, such secondary collisions from mega constellation satellites are also a significant threat to the Earth's geospatial environment, according to Tao et al, with the probability of collision for surrounding orbiting satellites exceeding the red alert threshold of 10 −4 within 30 min of a mega constellation satellite collision [16]. Oltrogge et al found that the situation in LEO space is not yet dire if properly managed; however, both LEO and GEO have substantial and persistent collision risks, and these collision risks, along with debris events, pose far-reaching and long-lasting effects [17].…”
Section: Introductionmentioning
confidence: 99%